Integration of Anti-Corruption Education in Civics Learning: A Case Study at SMPN 12 Makassar - Mustari, Mustari; MS, Hadyan Hashfi; Ridhoh, M Yunasri; Sanur, Iham Samudra; Rijal, Muh; Fadiyanto, Guruh Achmad (Universitas of Muhammadiyah Makassar, 2025)
This research departs from the urgency of education as a preventive tool to instill integrity values from an early age, amid the rampant corruption practices that are rooted in the social life of Indonesian society. The research aims to describe the integration of anti-corruption education in Pancasila and Civics Education (PPKn) learning, analyze the supporting and inhibiting factors in the process, and identify the impact on students at SMPN 12 Makassar. The approach used is qualitative with descriptive method. Data were collected through observation, in-depth interviews, and document analysis, then analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results showed that anti-corruption values were integrated through active learning approaches such as discussions, case studies, and value-based projects, as well as through the example of educators. Supporting factors for this integration include educators' commitment, principal support, and flexibility in curriculum development. Meanwhile, the obstacles faced include limited learning time and lack of special training for teachers. The impact of this integration can be seen from changes in students' behavior, such as increased honesty, sense of responsibility, discipline, and courage to voice injustice in the school environment. The findings confirm that anti-corruption education integrated in Civics learning contributes significantly to shaping learners' character with integrity, if implemented consistently and collaboratively.